Athletes` perceptions of performance enhancing substance user and non-user prototypes - Whitaker, L.; Long, J.; Petroczi, A.; Backhouse, S. H. (Performance Enhancement & Health, 2012)
This study explored athletes` perceived prototypes of performance enhancing substance (PES) users and non-users to facilitate a broader understanding of the risk/protective factors for doping use. Method